Was der Rheumatologe vom Dermatologen lernen kann: oder: Gute Freunde kann niemand trennen : Schnittpunkte der beiden Domänen = What the rheumatologist can learn from the dermatologist : or: nobody can separate good friends : Interfaces of both domains - Schäkel, Knut; Schirra, Astrid (Zeitschrift für Rheumatologie, 2018)
BackgroundRheumatology and dermatology are two medical disciplines, which are closely interwoven with each other.ResultsFrequent direct areas of cooperation are with psoriasis, psoriatic arthritis, connective tissue diseases and vasculitis. As a whole, chronic inflammatory diseases are frequently associated with cutaneous manifestations and require a specialized dermatological treatment. The diagnosis and treatment of adverse cutaneous reactions to systemic rheumatological treatment creates an additional area requiring a collaborative effort.ConclusionThe close cooperation between rheumatology and dermatology clinics, beeing established in many institutions, has many advantages for our patients, especially in those with a complex course of the disease. Furthermore, it presents a valuable opportunity to learn from each other. The successful establishment of inflammation centers in some larger hospitals is proof for the development of an intensified interdisciplinary treatment of patients.